Determination of Situations of Extra-curricular Practices Carried About Robotics, Coding and Electronics - Öz Yıldız, Reyhan; Talaslıoğlu, Seyide Senanur; Yıldırım, Mehtap (IBAD Sosyal Bilimler Dergisi, 2020)
In the study, it was aimed that the establishment of intramural and extracurricular practices carried regarding robotics, coding and electronics and the determination of teacher opinions on various subjects regarding robotics, coding and electronics. Within the context of this study, data was collected by teachers or administrators from 52 state schools in Avcılar district of Istanbul with the help of an online interview form. For examining the data collected in the study, descriptive analysis which is a kind of qualitative data analysis methods was used. Collected data was analysed in the frame of current situation determination, the determination of schools’ requirements, future plans of schools and the contribution of practices of robotics-coding and electronics into education. According to results of the study, it was determined that the use of practices of robotics, coding and electronics in intramural and extracurricular activities would provide a more effective learning environment for students and that it would contribute in a positive way to grow up individuals who use improving technology more effectively. In addition, common opinion of all schools that receive or want to receive education in these fields is that the practices of robotics and coding will make a positive contribution on students’ academic successes, attitudes and motivations.